Sharp edges led us here - Abraham, Danna; Abraham, Tarun (Murmurations: Journal of Transformative Systemic Practice, 2025)
This work explores the intersections of digital technology and creative poetic expression by integrating binary code as its artistic medium. Inspired by the duality embedded in binary constructs, the authors interrogate how unseen frameworks unify ideologies while perpetuating the damaging effects of singularity. Drawing on Gottfried Leibniz’s foundational binary systems, this piece metaphorically examines the pervasive role of binary operations in modern society. The poem’s binary translation integrates code writing using Python, as a part of combined efforts to make visible the boundaries that often prevent collaboration between technological and social disciplines. By playing with these structures, the authors advocate for a shift away from binary constructs toward embracing complexity, offering a transformative lens in hopes for the reconsidering of the systems that influence human lived experiences.